Identification of the slc45a2 gene that induces albinism in fishes of commercial interest for Peruvian - Scotto, Carlos (2024)
Albino fish have greater economic value than fish that have coloration both at the ornamental level and at the consumption level for their meat. Th e slc45a2 gene is associated with the induction of an albinism phenotype initially reported in Zebrafish (Danio rerio Hamilton, 1822) and Medaka fish (Oryzias latipes Temminck & Schlegel, 1846). With the information registered in the Genbank of the slc45a2 gene of the Tilapia fish (Oerochromis niloticus Linnaeus, 1758) and the Gamitana (Colossoma macropomum Bleeker, 1869), specific primers were designed in silico to identify this gene in these two freshwater species. Both sets of primers were used fi rst on these two species (Tilapia and Gamitana). And then tested in the fi sh Paco (Piaractus brachypomus Cuvier, 1818) and Oscar (Astronotus ocellatus Agassiz, 1831) whose slc45a2 gene sequences are currently unknown. With the set of primers designed for Tilapia, they gave a single band amplifi cation for the Tilapia and the Oscar. With the other set of primers designed for Gamitana, he amplified a band for both the Gamitana and the Paco. Both were approximately 120 nucleotides in size. The sequences obtained confirmedlevel for their meat. Th e slc45a2 gene is associated with the induction of an albinism phenotype initially reportedin Zebrafi sh (Danio rerio Hamilton, 1822) and Medaka fi sh (Oryzias latipes Temminck & Schlegel, 1846). With theinformation registered in the Genbank of the slc45a2 gene of the Tilapia fi sh (Oerochromis niloticus Linnaeus, 1758)and the Gamitana (Colossoma macropomum Bleeker, 1869), specifi c primers were designed in silico to identify this genein these two freshwater species. Both sets of primers were used fi rst on these two species (Tilapia and Gamitana). Andthen tested in the fi sh Paco (Piaractus brachypomus Cuvier, 1818) and Oscar (Astronotus ocellatus Agassiz, 1831) whoseslc45a2 gene sequences are currently unknown. With the set of primers designed for Tilapia, they gave a single bandamplifi cation for the Tilapia and the Oscar. With the other set of primers designed for Gamitana, he amplifi ed a band for both the Gamitana and the Paco. Both were approximately 120 nucleotides in size. Th e sequences obtained confi rmed